HISTORICAL SOCIOLOGY OF DISABILITY human validity and invalidity from antiquity to early modernity. - Hughes, Bill, 1956- ([S.l.] : ROUTLEDGE, 2019)
Covering the period from Antiquity to Early Modernity, A Historical Sociology of Disability argues that disabled people have been treated in Western society as good to mistreat and - with the rise of Christianity - good to be good to. It examines the place and role of disabled people in the moral economy of the successive cultures that have constituted Western civilisation'. This book is the story of disability as it is imagined and re-imagined through the cultural lens of ableism. It is a story of invalidation; of the material habituations of culture and moral sentiment that paint pictures of disability as what not to be'. The author examines the forces of moral regulation that fall violently in behind the dehumanising, ontological fait accompli of disability invalidation, and explores the ways in which the normate community conceived of, narrated and acted in relation to disability. A Historical Sociology of Disability will be of interest to all scholars, students and activists working in the field of Disability Studies, as well as sociology, education, philosophy, theology and history. It will appeal to anyone who is interested in the past, present and future of the last civil rights movement'.
List of figures; List of tables; Acknowledgements; INTRODUCTION; Violating disability; Chapter outlines; Concluding remarks; PART 1: Method and Theory; CHAPTER 1: Thinking through disability history: An act of recovery; Introduction; Methodological self-consciousness: The author in the confessional; New Historicism; The place of Proprium and moral economy in a historical sociology of disability; History of disability or a history of impairment; Concluding remarks; CHAPTER 2: Modelling disability theory: A contemporary history of the disability idea; Introduction; First wave radicalism: The social model of disability; The second wave: Conceptual proliferation, Critical Disability Studies and the growth of the cultural model of disability; Concluding remarks; CHAPTER 3: Conceptualising property and propriety, validity and invalidation; Introduction; Recognition: Moral economy of propriety; Ableism: the cloak of validity; Invalidation; Concluding remarks; Part 1: Concluding remarks; PART 2: Disability in History: Antiquity, the Middle Ages and Early Modernity; Part 2: Introductory remarks; CHAPTER 4: Disability in ancient Greece and Rome; Introduction; Arete: The contours of classical propriety; 'And those of the worst': Disposable bodies; Pharmakos: The disabled scapegoat; An ocular-centric culture of light and appearance: being blind in Greco-Roman society; Concluding Remarks; CHAPTER 5: Disability in the Christian Middle Ages; Introduction; Eristic Christianity; God, Church and state: Normate power triangulated; Theological invalidations: The others of the unscathed; Ambiguous God, ambiguous scripture, ambiguous testaments of sin and disability; God's tease: Saints and sinners; No ears to hear, no eyes to see ... the wonders of God; The era of ridicule; From monsters to demons; Merciful conduct: A stairway to heaven; Concluding remarks; CHAPTER 6: Renaissance and Reformation: Disability invalidation in Early Modernity; Introduction; Interregnum; Aesthetics and classical revivalism; Demons and witches; Monsters; Dark subjects; Savages and heathens; Social dislocation: Vagabonds and beggars; Fools and folly; 'Each to his own': The closed Protestant body; Concluding remarks; CONCLUSION: A banquet of indignities; Index
OCLC-licensed vendor bibliographic record.
Keywords: Sociology of disability -- History; HISTORY / Social History; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Handicapped